Corruption and the shadow economy - Jay Pil Choi; Marcel Thum (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
This paper develops a simple framework to analyze the links between corruption and the unofficial economy and their implications for the official economy. In a model of self-selection with heterogeneous entrepreneurs, we show that the entrepreneurs' option to flee to the underground economy constrains a corrupt official's ability to introduce distortions to the economy for private gains. The unofficial economy thus mitigates government-induced distortions and, as a result, leads to enhanced economic activities in the official sector. In this sense, the presence of the unofficial sector acts as a complement to the official economy rather than a substitute.
Keywords: D9; H2; K4; L1; 330; corruption; shadow economy; official economy; self-selection; Korruption; Schattenwirtschaft; Wohlfahrtseffekt; Theorie